Komite Audit, Profitabilitas, Solvabilitas, dan Ketepatan Waktu Pelaporan Keuangan Perusahaan Manufaktur-Sektor Logam - Bahtiar Effendi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
This study aims to determine the effect of audit committees, profitability, and solvability on the financial report punctuality of metal manufacturing companies listed in the Indonesia stock exchange. This study used quantitative approach. The data collection technique used in this study is document analysis in the form of financial statements of metal subsector manufacturing companies listed on the Stock Exchange for the 2014-2016 period accessed from www.idx.co.id. The sampling technique used was purposive sampling with a total sample of 30 companies. The data analysis method used was multiple linear regression analysis performed in SPSS 24.0 program. The results showed that (1) audit committees do not significantly affect the punctuality in submitting financial statements. (2) Profitability (ROA) has a negative effect or no significant effect on the financial reporting punctuality, (3) Solvability does not significantly influence the financial reporting punctuality (3).